A comparison of health behaviours in male adolescents with and without offending histories referred for adolescent health services in Turkey. (12th November 2022) - Ayaz, Nusret; Karatoprak, Serdar
Abstract: Background: Offending and incarceration are important societal problems that might be reduced by improving early intervention. Most prior work identifying risk factors has focussed on early oppositional or aggressive behaviours and environmental problems. Among adults, it is well recognised that offenders have much poorer health than the wider population. This raises questions about whether behaviours that put health at risk while a teenager may also be good markers of subsequent offending. Aims: To examine the relationship between risky health behaviours and delinquency by comparing male teenage offenders with a history of incarceration and male teenagers with no criminal involvement. Methods: In this cross‐sectional study, 66 male 12–18‐year‐old offenders with an incarceration history who were referred for evaluation to the Forensic Medicine Polyclinic in 2021 were compared with 74 similar aged adolescents without a criminal record but attending another clinic in the same hospital, using the Risky Health Behaviour Scale (RHBS). This covers dietary, road safety and sexual behaviours as well as exercise, substance use and violent behaviours. Negative items were reverse scored so that higher scores indicated more pro‐health activities. Results: Total RHBS scores were significantly lower among the offender‐group than the comparison teenagers (Means 93.19 ± 17.00: 107.20 ± 10.83; p ≤ 0.001). This reflected significant differences in each of the subscale scores except dietary and risky sexual behaviour. Only substance use behaviours, however, were independently related to offender group membership, as was family socio‐economic status. Conclusions: Our findings add indications of risky health‐related behaviours to the already extensive literature on risky social behaviours in the history of young offenders. It is possible that focussing on young offenders referred to a health service, albeit one primarily directed at mental health, has exaggerated such differences, but if substantiated in larger and more diverse samples, these findings may open new avenues for early identification of young people at risk of offending and commensurate early interventions. Focus on substance use by young people seems especially important, but low family socio‐economic status needs remedies too.